Coral-based climate reconstructions of Western Pacific warm pool for the past - 280 years - Ahmad Taufiq Mohamed Mohtar (Nanyang Technological University, 2022)
The Western Pacific Warm Pool (WPWP) large warm water mass contributes to atmospheric heat and moisture, modulating El Niño-Southern Oscillation (ENSO) phase changes, potentially leading to global climate extremes. Researching WPWP climate variability will improve understanding of ENSO and the behavior of longer timescale climate drivers. However, the lack of long, continuous and high-resolution instrumental climate observations within the WPWP limits understanding of its past climate changes. Massive corals from the WPWP allows past climate reconstruction characterizing the warm pool spatiotemporal and hydrology changes beyond instrumental timescales. A better understanding of these processes and their underlying climate drivers allows for better evaluation of regional trends, climate connections to global regions, and climate predictions in response to global warming. Porites spp. coral cores sampled from Kosrae island (KOS) and Woleai atoll (WOL), located on separate sites of Federated States of Micronesia, capture the opposite dipole signal of ENSO. Each coral core was slabbed and x-rayed to reveal images of annual density banding to assist in determining sampling axis and age assignment. The slabbed coral cores were analyzed for δ18Oc and Sr/Ca proxies for sea surface temperature (SST) and salinity (SSS), respectively. Monthly resolved reconstructed SST and SSS spanning 165 and 277 years were generated from KOS and WOL, respectively. The Sr/Ca-based reconstructed SST from KOS and WOL display the expected ENSO dipole signal. The difference between these records generates the zonal SST gradient, KOSWOLSST, capturing the warm pool's east-west zonal migration during ENSO events. The extended KOSWOLSST century exhibit ENSO’s spatiotemporal SST influence on the WPWP dating back to the mid-19th century. At decadal timescales, separate KOS SST displays consistent variability to the IPO. However, WOL SST exhibit strong influence driven by the Northern Hemisphere SST. Extending the WOL SST record further ~110 years allow examination of centennial-scale SST variability. Significant power and centennial relationship between extended WOL SST to a South china sea paleo SST record indicates simulated Pacific Centennial Oscillation (PCO) observed in controlled coupled global climate simulation (cGCMs) exists in nature. These findings collectively establish a centennial-scale natural SST forcing in the WPWP that potentially impacts global teleconnections.The δ18Oc-based reconstructed KOS and WOL SSS reflect each site’s precipitation driven changes. The averaged SSS records generate KOSWOLSSS, an index representative of the regional WPWP precipitation. Separate KOS and WOL SSS records dating back to the mid-19th century indicates WPWP experienced increasing precipitation changes leading to freshening trends driven by global warming. Extending WOL SSS records further ~110 years allows examination of WPWP centennial driven SST variability (PCO) influence on WOL SSS. Significant WOL SSS and SST relationship indicate during SST increases saw a decline in precipitation. This and antiphase centennial SST relationships between Micronesia and Vietnam suggest a robust precipitation footprint of the PCO. This thesis derived a WPWP zonal SST gradient, regional hydrological records, established WPWP climate SST and SSS climate drivers and verified the presence of PCO and its precipitation footprint based on coral proxy records. These key findings underscore the need to investigate natural climate driver(s) variability within the WPWP. Furthermore, incorporating the PCO variability and its precipitation footprint in cGCMs is crucial to modelling future climate as climate changes within this region impact global teleconnections and tropical Pacific regional hydrology.